Penciptaan Teater Tubuh - Supartono, Tony (PANGGUNG, 2016)
ABSTRACTÃÂ The ÃÂ process ÃÂ of creative ÃÂ of theatricalÃÂ ÃÂ  body is an offer of renewal ÃÂ theatre ÃÂ by exploring and processing ÃÂ the body, which become the main ÃÂ key in theatre production.ÃÂ  ÃÂ This paper proposed the design to offer new thinking, ÃÂ and alternative ÃÂ thinking.Creative ÃÂ of theatrical ÃÂ bodyis a process ÃÂ of body practice ÃÂ with the body consciousness ÃÂ either ÃÂ as an idea or the body itself ÃÂ as the idea, the learning ÃÂ process of the body until get the consciousness ÃÂ movements which resulted by the body. For ÃÂ the process of practice ÃÂ the researcher ÃÂ called it as Ã¢â¬ÅActorÃÂ  Body InterrogationÃ¢â¬Â ÃÂ that is the process of breaking ÃÂ and re-asking ÃÂ the problem of actorsÃ¢â¬â¢ ÃÂ body.Creative ÃÂ of theatrical ÃÂ body offers new point ÃÂ of view about ÃÂ the body, which not only as the expression media, but the body itself stands ÃÂ alone as its identity. The body is considered ÃÂ as the phenomenaÃÂ  ÃÂ which stand ÃÂ alone and also making relationship to the environment, ÃÂ spaces, build- ings, vehicles, peoples, even to the society ÃÂ and their ÃÂ ideology which dominant. ÃÂ Therefore, cre- a t i v e ÃÂ o f ÃÂ t h e a tr i ca l b o d y i s a p ro ce s s o f ÃÂ com p l e t e ÃÂ t h e a t re ÃÂ b e t we e n a ct o r, ÃÂ a n d ÃÂ t h e ÃÂ b o d y laugaugeinclude its relationship to the society.ÃÂ Keyword: ÃÂ theatre, ÃÂ body, body interogation,ÃÂ  ÃÂ public ÃÂ spaceÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Proses penciptaan teater tubuh merupakan penawaran pembaharuan teater dengan menggarap dan mengolah tubuh, yang menjadi kunci utama produksi teater. Paper ini mengajukan rancangan untuk menawarkan pikiran-pikiran baru, pikiran-pikiran alternatif. Penciptaan teater tubuh adalah proses latihan tubuh dengan kesadaran tubuh sebagai gagasan atau tubuh itu sendiri sebagai ide, proses belajar pada tubuh sehingga mendapat kesadaran gerak-gerak yang dilahirkan oleh tubuh. Proses latihannya penulis memberi nama Ã¢â¬Åinterogasi tubuh aktor Ã¢â¬Â, yaitu proses membongkar dan mempertanyakan kembali persoalan tubuh aktor.Penciptaan teater tubuh menawarkan pandangan baru tentang tubuh yang bukan sekedar media ungkap tetapi tubuh itu sendiri mandiri sebagai sebuah identitas. Tubuh dipandang sebagai fenomena yang berdiri sendiri tetapi sekaligus melakukan relasi dengan lingkungan: jalan, bangunan, kendaraan, orang-orang dan bahkan seluruh masyarakat dan ideologinya yang sedang dominan. Dengan demikian penciptaan teater tubuh adalah proses teater yang utuh antara aktorÃÂ ÃÂ  dan bahasatubuh sekaligus relasinya dengan masyarakat.ÃÂ Kata kunci : teater, tubuh, interogasi tubuh, ruang publik.